Kiai & budaya korupsi di Indonesia - Umam, Ahmad Khoirul; Junaidi, Akhmad Arif (Semarang, Indonesia : RaSAIL, 2006)
Culture of corruption in Indonesia
Daftar pustaka : p. [201]-219
Keywords: Corruption -- Indonesia; Bribery -- Indonesia; White collar crimes -- Indonesia